Nonstationary heat equation with nonlinear side condition - Belickas, Tomas; Kaulakytė, Kristina; Puriuškis, Gintaras (Mathematical Modelling and Analysis, 2025)
The initial boundary value problem for the nonstationary heat equation is studied in a bounded domain with the specific overdetermination condition. This condition is nonlinear and can be interpreted as the energy functional. In present paper we construct the class of solutions to this problem.